(3eONd Edi EOQGL GdahdcdhQ GdehSjbj GddHfGfj aj GdJQHjI GdehSjbjI deQMdI GdJYdje GdCSGSj, GdMdbI GdKGfjIs - (3eQYH, eGZGdjs ((3HjQhJs (3LGeYI GdQhM GdbOS (B- (3GdcSdjc (B((3dHfGf(B) - (3cdjI GdehSjbis, 2010)
(3LGA GgJeGe gPg GdOQGSI HGdahdcdhQ GdehSjbj GddHfGfj ef MjK EONGdg aj GdJQHjI GdehSjbjI deQMdI GdJYdje GdCSGSj, GdMdbI GdKGfjI, aj SHjd EZfGFg HGdOQLI GdGhdi, hdcj dG jfOKQ hjRhd Hd djMGaX Ydjg hjfbd ddCLjGd(B. (3JJqQcR gPg GdOQGSI Ydi cjajI GdMaGX Ydi GdCZGfj GdahdcdhQjI GddHfGfjI hEMjGFgG, ef NdGd JcjjagG TYQjG hJMdjdjG, hEOQGLgG aj GdefGgL GdehSjbjI GdeOQSqjI(B. (3hef NdGdg, jJYQa GdWGdH Ydi GdCLfGS hGdEjbGYGJ GdYQHjI GdeSJNOeI, hYdi YOO ef GdfXQjGJ GdehSjbjI GdCNQi(B. (3Jcef CgejI gPg GdOQGSI chfgG OQGSI TGedI dhGbY GdahdcdhQ GddHfGfj aj GdefGgL GdehSjbjI GdeSJNOeI aj GdeOGQS GdQSejI hGdNGUI, CdG hgj Jcjja cdeGJ GdCZGfj GdJQGKjI GddHfGfjI MSH ehGVjY JQHhjI eQJHWI HYeQ GdWad, eSJhGg GdacQj hbOQJg Ydi GdZfGA hGdMaX, hJHSjW GddMf GdahdcdhQj hGSJNQGL GdfXQjGJ GdehSjbjI efg(B. (3JYJeO gPg GdOQGSI Ydi GdefgLjI GdhUajI hGdJMdjdjI, HGdEVGaI Edi CfgG JYWj fHPI JGQjNjI Yf GdJQHjI GdehSjbjI, Yf GdahdcdhQ GddHfGfj hYf GdCZGfj GdJQGKjI GdeOQhSI, EVGaI Edi JSLjd GdfeGPL GdLOjOI ddCZGfj GdahdcdhQjI GddHfGfjI, GdJj OQSJ hMddJ HCUhGJ eLehYI ef WdqGH KGfhjI QGgHGJ GdhQOjI HdGW(B/ (3LHjd, ef GdUaha GdGHJOGFjI hGdJcejdjI(B. (3hbO NJeJ GdOQGSI HYQV TGed dHYV GdCZGfj GdJQGKjI GddHfGfjI, ef MjK GdCUd, GdJGQjN, GdHfjI, GdhRf, GdCOGA, GddMf, ceG YQV feGPL efgG, EVGaI Edi GbJQGM feGPL ZfGFjI NGUI HcdeGJ LOjOI JfGSH YeQ WdqGH GdeQMdI GdeNJGQI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle primaire L$1 (Benseignement de La Musique, des chansons et la dance Curriculums; Elementary Education Teaching Music & Songs &Dance Curricula; (3GdeQMdI GdGHJOGFjI JYdje GdehSjbi hGdCZGfj hGdQbU GdefGgLs